Literatur Review: Pengembangan dan Optimalisasi Media Pembelajaran PowerPoint Interaktif Berbasis Canva untuk Meningkatkan Motivasi Peserta Didik di Era Digital dalam Materi Momentum Impuls - Eka Mardiana; Dina Larasati; Alifia Rohmah; Dona Febri Enjelina; Manfaatun Nisa; Risma Ayunda Putri; Ellianawati (Unnes Physics Education Journal, 2025)
The deployment of digital learning media is becoming an increasingly pivotal aspect of the field of physics education, particularly in enhancing students' motivation and comprehension of abstract concepts such as momentum and impulse. Technological advancements have led to the use of software like Canva to create interactive PowerPoint presentations, which have improved the quality of learning. The objective of this study is to assess the efficacy of Canva-based learning media in the context of physics education. This study employed a systematic review with a bibliometric approach, whereby data were gathered from the Scopus database between 2014 and 2024. The selection of pertinent articles was conducted in accordance with the PRISMA method, which encompasses the following stages: identification, screening, eligibility, and inclusion. In order to ensure the quality and relevance of the selected articles, the inclusion and exclusion criteria were applied at each stage. The data were analyzed using VOSviewer with the objective of mapping research trends and interrelationships between variables. The results demonstrated an increase in publications related to Canva-based digital learning media, with the majority originating from Indonesia. The utilization of Canva has been demonstrated to enhance student motivation and engagement in physics learning, particularly at the secondary school level. However, it is essential to acknowledge the limitations of this digital learning medium.